2015
DOI: 10.1007/s11082-015-0222-2
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence quenching of Rhodamine 6G with different concentrations by laser ablated gold nanoparticles

Abstract: Colloidal gold nanoparticles are prepared by laser ablation method and characterized by UV-Visible spectrometry and Transmission Electron Microscopy. Fluorescence quenching of Rhodamine 6G dye with different concentration, from 0.05 to 15 lM, in the presence of gold nanoparticles have been investigated. The optical absorption and fluorescence emission of samples are studied. Shift of the fluorescence peaks in the presence of gold nanoparticles are the same as the absorption peaks for different concentrations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Presence of the metallic structures in the vicinity of the fluorophore can alter the optical properties of the fluorophore. There have been some attempts to show both quenching and enhancement of the fluorescence intensity of fluorophore can be introduced by NPs [13]. Kumar et al (2014) [14] studied both quenching and enhancement of the fluorescence intensity of the Rh6G with different dye concentrations, ranging from 3 to 300 µM, in presence of 15 nm diameter Au NPs.…”
Section: Polyvinyl Alcoholmentioning
confidence: 99%
“…Presence of the metallic structures in the vicinity of the fluorophore can alter the optical properties of the fluorophore. There have been some attempts to show both quenching and enhancement of the fluorescence intensity of fluorophore can be introduced by NPs [13]. Kumar et al (2014) [14] studied both quenching and enhancement of the fluorescence intensity of the Rh6G with different dye concentrations, ranging from 3 to 300 µM, in presence of 15 nm diameter Au NPs.…”
Section: Polyvinyl Alcoholmentioning
confidence: 99%
“…A large number of publications have been reported that when such a dye solution is mixed with Au MNPs, it possess a strong plasmon field. Its fluorescence emission also might quench or enhance extensively [5][6][7]. Our study is to better gain insight into this phenomenon and predict the extent of quenching and/or enhancement of fluorescence in terms of FP measurement.…”
Section: Introductionmentioning
confidence: 99%